Being Small and Outnumbered: Service and Sociocultural Exclusion Among Older Linguistic Minorities in Finland - Nyqvist, Fredrica; Björklund, Siv; Lindell, Marina; Nygård, Mikael (Minorités linguistiques et société / Linguistic Minorities and Society)

(untitled) (Institut canadien de recherche sur les minorités linguistiques / Canadian Institute for Research on Linguistic Minorities, 2021)
Our study aims to analyze the social exclusion of older Swedish and Finnish speakers living as linguistic minorities in bilingual municipalities in Finland, where municipal authorities are required to offer services in both languages. Data was taken from the 2016 Language Barometer Survey, measuring the quality of language services in bilingual municipalities (n=33). For the purposes of our study, we focused on 2,030 people between the ages of 60 and 84. We included four different language groups, unilingual Swedish and Finnish speakers and Finnish-Swedish bilinguals and examined two social exclusion domains: service and sociocultural exclusion. The results showed that living as a regional minority poses a greater challenge when it comes to social inclusion for the unilingual and bilingual Swedish minority, as opposed to the Finnish-speaking minority. We conclude that linguistic rights seem to be achieved in the most egalitarian way in bilingual municipalities where Swedish is the majority language.